State dependence in the finance-growth nexus: A functional coefficient approach - Helmut Herwartz; Yabibal M. Walle (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
Noting that 'one size does not fit all' in the case of the finance-growth (FG) nexus, a growing body of literature has recently focused on uncovering economic conditions under which financial development could be beneficial (detrimental) to economic development. We look into these conditions by means of a flexible semiparametric approach which allows the long-run FG nexus to depend on measurable economic states. Using annual data for 74 economies spanning the period 1975-2005, we find that the level of financial development shows a strong positive impact on the FG nexus. Moreover, although the impact of finance on growth is generally higher in high-income economies, allowing for intra-group variations reveals scenarios where the impact could be higher in low-income economies. However, the FG link could also be negative if low- and lower-middle-income economies have very large governments or are extremely open to international trade.
Keywords: C14; C33; O16; G28; 330; finance-growth nexus; financial development; economic growth; functional coefficient model